ECONOMIC GROWTH, HEALTH EXPENDITURE AND HUMAN DEVELOPMENT IN ASIA - Fariastuti 1), Fariastuti 1) (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2011)
The main objective of this paper is to describe typology of the relationship between economic growth and health expenditure respectively and human development. To answer this objective, this study utilized data from the 2009 Human Development Report. The data has been analyzed by using typology method. Finding in this study shows that the high income countries tend to concentrate in human development lopsided cycle while the lower middle income countries tend to concentrate in the vicious cycle. The study concludes the importance of quality of economic growth and both amount and the effectiveness of health expenditure in improving human development. The high economic growth and the high health expenditure which are not accompanied by the better quality will not be able to guarantee the countries to have a high human development. Keywords: Economic Growth; Human Development; Health Expenditure, Asia.